Through the eyes of Peter Pan: internalizing mental illness via animation in the documentary "Life, Animated" - Tscheschel, Janin; Justus Liebig University Giessen (My University, 2021)
This article discusses to what extent the documentary film, through its aesthetic strat-egies and narrative style, spotlights the topic of mental illness, contributing to soci-ety s acceptance of this taboo topic. The 2016 documentary Life, Animated, which integrates animations into its presentation, gives insights into the concrete possibilities of negotiating the topic of mental disorders. A discourse-analytical examination em-beds the film in a larger context and focuses on the crisis of the documentary film under the sign of hybrid forms combining fact and fiction. The article shows how these hybrid formats both question the documentary film s claim to reality and offer the opportunity to find images conveying inner states, and highlights that an extension of the possibilities of representation, such as the integration of animation in documen-taries, allows conditions that are completely unknown to the viewers to be immer-sively experienced, thereby contributing to their de-stigmatization.
Keywords: mental illness; animation; documentary; fact; fiction; ddc:300